A Genome‐Wide Association Study Identifies a Candidate Gene Associated With Atazanavir Exposure Measured in Hair. Issue 5 (8th February 2018) - Tamraz, Bani; Huang, Yong; French, Audrey L.; Kassaye, Seble; Anastos, Kathryn; Nowicki, Marek J.; Gange, Stephen; Gustafson, Deborah R.; Bacchetti, Peter; Greenblatt, Ruth M.; Hysi, Pirro G.; Aouizerat, Bradley E.
Abstract : Hair provides a direct measure of long‐term exposure of atazanavir (ATV). We report the results of the first genome‐wide association study (GWAS) of ATV exposure measured in hair in an observational cohort representative of US women living with HIV; the Women's Interagency HIV Study. Approximately 14.1 million single nucleotide polymorphisms (SNPs) were analyzed in linear regression‐based GWAS, with replication, adjusted for nongenetic predictors collected under conditions of actual use of ATV in 398 participants. Lastly, the PharmGKB database was used to identify pharmacogene associations with ATV exposure. The rs73208473, within intron 1 of SORCS2, resulted in a 0.46‐fold decrease in ATV exposure, with the strongest association ( P  = 1.71×10 −8 ) in GWAS. A priori pharmacogene screening did not identify additional variants statistically significantly associated with ATV exposure, including those previously published in ATV plasma candidate pharmacogene studies. The findings demonstrate the potential value of pharmacogenomic GWAS in ethnically diverse populations under conditions of actual use.